The Future Looks Good: Examining the Associations Between Coping, Psychological Distress, and Optimism - Santos, Tiago; Uva, António de Sousa; Rodrigues, José Fernandes; Ferreira, Regina; Monteiro, Diogo; Hernández-Mendo, Antonio; Rodrigues, Filipe (Frontiers in Psychology, 2022)
The recent pandemic and consequent lockdown had a substantial impact on mental health and optimism regarding the future. Previous research showed that levels of depression, anxiety, and stress had increased throughout the pandemic. Nonetheless, how individuals cope when faced with adversity may be associated with positive expectations regarding the future. A sample of 274 Portuguese workers (female = 54) with a mean age of 40.86 (SD = 0.70) and work experience of 19.68 years (SD = 12.07) met inclusion criteria and agreed to participate in the proposed study. They represented a variety of working classes (i.e., arts, engineering, marketers, transportation and logistic, clerks, personal trainers, managers, lawyers, accountants, directors, journalism, health care). We investigated the associations between depression, stress, anxiety, adaptive and maladaptive coping, and optimism while controlling for working experience, gender, and work type. We found that depression was related to lower levels of optimism. However, for participants scoring high on adaptive coping and anxiety, higher scores of optimism were reported. Gender, work type, and experience did not significantly influence the results. These results provide evidence through which positive mental health can be promoted after the pandemic.